Algunos instrumentos fiscales para reforzar las políticas de suelo - Kunz Bolaños, Ignacio; Eibenschutz Hartman, Roberto (El Colegio de México A.C., 2001)
This article describes a series of local fiscal instruments for reinforcing urban development policies, particularly those involving land. The main aim of these instruments is to promote inner city development while preventing speculation and the waste of urban space. As one of its theoretical bases, the article explains the general mechanism of intervention for transferring the undesirable costs of the poor use of the city to those responsible for this through fiscal measures. It then describes the instruments used; zoning-based appraisal, imposing proportionally higher taxes for land than for construction; taxing the under-use of standards and levying a surcharge on wasteland. Much of the analysis described is based on reality and examples from the Federal District, although the measures discussed are applicable to a variety of situations.